2003
DOI: 10.1038/sj.ejcn.1601692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enhanced consumption of fruit and vegetables on plasma antioxidant status and oxidative resistance of LDL in smokers supplemented with fish oil

Abstract: Objective: To determine whether consumption of five portions of fruit and vegetables per day reduces the enhancement of oxidative stress induced by consumption of fish oil. Subjects: A total of 18 free-living healthy smoking volunteers, aged 18-63 y, were recruited by posters and e-mail in The University of Reading, and by leaflets in local shops. Design: A prospective study. Setting: Hugh Sinclair Unit of Human Nutrition, School of Food Biosciences, The University of Reading, Whiteknights PO Box 226, Reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 40 publications
0
23
2
Order By: Relevance
“…Also some but not all other studies have reported that intake of n-3 fatty acids promote increased peroxidation of LDL (Pedersen et al, 2003;Piolot et al, 2003;Roberts et al, 2003). In the present study, the rate of LDL oxidation was significantly higher in nonsmokers than in smokers, whereas the lag phase of LDL oxidation did not differ significantly between the groups at baseline.…”
Section: After Vitamin E Supplementationcontrasting
confidence: 63%
See 2 more Smart Citations
“…Also some but not all other studies have reported that intake of n-3 fatty acids promote increased peroxidation of LDL (Pedersen et al, 2003;Piolot et al, 2003;Roberts et al, 2003). In the present study, the rate of LDL oxidation was significantly higher in nonsmokers than in smokers, whereas the lag phase of LDL oxidation did not differ significantly between the groups at baseline.…”
Section: After Vitamin E Supplementationcontrasting
confidence: 63%
“…Ex vivo measures of LDL resistance to oxidation have shown significant increases even at low doses of alpha-tocopherol (43-200 mg/day) (Princen et al, 1995;Maskarinec et al, 1999;Upritchard et al, 2003). Antioxidant supplementation or increased consumption of fruit and vegetables has been reported to reduce the susceptibility of LDL to oxidation also in smokers (Princen et al, 1992;Roberts et al, 2003). In fact, beneficial effects of vitamin E supplementation on atherosclerosis may be the most relevant to persons with initially low serum levels of vitamin E. In this study, the lag phase of LDL oxidation prolonged significantly in both the study groups, smokers and nonsmokers after 8 weeks supplementation of vitamin E. Moreover, the effect of vitamin E was greater in smokers than in nonsmokers, which has also been reported by Salonen et al (2003).…”
Section: After Vitamin E Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in dietary PUFA, however, has been a concern for antioxidant status in diabetes (12), but blood levels of antioxidants in people with diabetes appear related to serum lipids, not dietary intake, with products of oxidative damage more linked to intakes of SFA and cholesterol and to levels of endogenous antioxidants (44). In the case of large doses of fish oil supplements, a decreased oxidative stability of plasma and LDL has been demonstrated in healthy subjects, but this was offset by including five portions of fruit and vegetables in the daily diet (45). In our study, SFA intakes were kept low, and five portions of fruits and vegetables were included in the dietary advice.…”
Section: Dietary Intakementioning
confidence: 99%
“…The antioxidant efficiency of vitamin E appears to be greatly enhanced by regeneration of the vitamin from its oxidised products (143). Appreciation of other antioxidants (144)(145)(146) has developed the notion that while vitamin E protects lipids other antioxidants must recycle vitamin E. The other major antioxidants are coenzyme Q and vitamin C (147,148) Regeneration of a-tocopherol from its tocoperoxyl radical have been demonstrated by vitamin Another explanation for the low levels of cc-TQ in tissues is that the tocopherol may be one of the last antioxidant substances to be consumed during oxidative stress. Burton and Ingold, found that other antioxidants such as sulphydryl groups in proteins were found to be used preferentially to tocopherols during oxidations initiated by free radicals in human plasma (28,153).…”
Section: ) Vitamin E Is Poor Inhibitor Of Reactions 1 and 2 (123)mentioning
confidence: 99%